Pyrolytic oil from fluidised bed pyrolysis of oil palm shell and its characterisation - Islam, Mohammad Nurul; R. , Zailani; Ani, Farid Nasir (Elsevier B V, 1999)
Biomass in the form of oil palm shell was pyrolysed in an externally heated 5 cm diameter. 30 cm high fluidised bed pyrolysis reactor with nitrogen as the fluidising gas and silica sand as the bed material. The pyrolysis oil was collected in a series of condenser and ice-cooled collectors. The char was collected separately while the gases were flared. The effects of process conditions, like fluidised bed reactor temperature, feed size and fluidisation gas flow rate on the product yields were studied. The product yields were found to be significantly influenced by the process conditions. The composition of oil was determined at fluidised bed temperature of 500Â°C at which the liquid product yield was maximum. The oil was analysed by Fourier Transform infra-red (FTIR) spectroscopy and gas chromatography/mass spectrometry (GC/MS) techniques. In addition, the physical properties of the oil were determined. The results showed that the oil was highly oxygenated containing a high fraction of phenol-based compounds. Detailed analysis of the oil showed that there was no concentration of biologically active polycyclic aromatic species in the oil. A brief preliminary economic analysis is presented at the end of the paper (see Appendix).